Effect of Anti-Felting Treatment on Thermal Comfort Properties of Selected Wool Fabrics in Wet State (Journal of Fiber Bioengineering and Informatics, 2013)
Wool fabrics both in dry and wet state exhibit high thermal insulation and dry touch, but their maindisadvantage - felting, caused by exposition of the fabrics to mechanical action under hot-wet state, mightlimit their generally excellent properties. Therefore, antifelting treatment is often used to avoid the fabricfelting. However, when the level of antifelting treatement is exaggerated, thermal comfort properties ofwet wool fabrics might get reduced. In the paper, the effect level of various antifelting treatments onthermal comfort properties of wet wool fabrics was studied with the objective, to determine the levelsof treatment, allowing the reduction of the felting behaviour and simultaneously maintain the excellentthermal insulation and thermal contact properties of wool fabrics.